Verification of Performance in Results-Based Financing : The Case of Afghanistan - Cashin, Cheryl (World Bank, Washington, DC, 2016)
The Ministry of Public Health in Afghanistan implements a supply-side results-based financing (RBF) scheme to improve the provision of a standardized basic package of health services (BPHS) to its population. Contracting NGOs and “contracting-in” MOPH providers, this RBF program concentrates on high-priority maternal and child health services in the BPHS such as antenatal care (ANC), post-natal care (PNC), delivery care, nutrition, immunization coverage, tuberculosis (TB), as well as quality of care. It includes an intensive data verification method, focusing on both the quantity and the quality of delivered services, which was implemented between 2010 and 2013 by international third party organizations. This verification method was specifically used to ensure that providers reach performance thresholds and disburse performance payments. This case study describes the major characteristics of this RBF verification method. Taking stock of the experience of the MOPH, it aims at generating possible lessons for other RBF initiatives, thereby expanding knowledge and making RBF verification processes more efficient, sustainable and effective. This case study also responds to concerns about the future sustainability of RBF, particularly with regard to the intensive and external nature of verification